Freud's literary culture - Frankland, Graham (Cambridge studies in German., 2000)
This original book investigates the role played by literature in Sigmund Freud's creation and development of psychoanalysis. Graham Frankland analyses the whole range of Freud's own texts from a literary-critical perspective, providing a comprehensive reappraisal of his life's work.